The elusive ‘promised land’: South Africa’s rural community struggles after thirty years of democracy - Theodore Nkadimeng Mahosi (Interdisciplinary Journal of Rural and Community Studies, 2025)
This study highlights the struggles of Black South Africans in rural communities, which define inequalities and socio-economic conditions thirty years after the first democratic elections in 1994, regardless of the ANC's promise of “a better life for all.” The purpose of discussing these challenges was to explore selected areas relevant to these issues as a delimitation. A closer look at the socio-economic history of a people reveals factors and circumstances that either promote, sustain, or challenge the livelihoods of a society or community, as in South Africa, race and geographical location define social status and quality of life. Such circumstances have particularly affected Black South African rural communities, who continue to experience abject poverty and destitution. This points to a departure from the Batho Pele Principles, which aimed to focus on socio-economic development programmes. The data used was ‘desktop’ from secondary sources, reports, and policy papers deemed relevant to the study and related to the experiences and struggles of rural communities against inadequate education, sustainable livelihoods, water and sanitation, and health, among others. The study concluded that, despite the gains of democracy, more needs to be done. An Afrocentric perspective was preferred because it is suitable for conceptualising, operationalising, and understanding social human problems such as rural community struggles outside the confines of Eurocentric knowledge ‘paternalism’. An Afrocentric method was used to present the findings of the study, based on the identified subtopics.